IMPLIKASI HERMENEUTIS DAN PEDAGOGIS PERBEDAAN PEMAHAMAN AYAT-AYAT KINAYAH DALAM AL-QURâ€™AN - Nurbayan, Yayan (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2009)
In The Koran there are some ayahs using kinayah style. This kind of ayah is interesting to analyze, because it is complicated and draw some controversies of interpretation among the interpreter. Some questions raised here: what is the basic meaning of â€œkinayahâ€ in Koran? What is the hermeneutical and pedagogical implications of the different interpretation towards the kinayah ayahs in Koran? How many kinayah ayahs according to the interpreter (mufassir)? This research shows that the number of kinayah ayahs according to Wahbah Zuhaili is sixty five ayahs; Shobuny said it is sixty four ayahs, Qurtuby 999 ayahs, and Thabary 899 ayahs. The difference of number is cause by different concept of kinayah they use. This research shows that the kinayah ayah in Koran in general have to be understood connotativel